2006
DOI: 10.2109/jcersj.114.189
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Stability and Mechanical Properties for Ceramic Composite Films Coated on Steel by Wet Process

Abstract: ᛘᗕǺȗș̥ኑˀǺΰ⓯ǦǮ⓹۰ɃɱɧɋȷℋǽᡡયමǷᑿ፦ᣀමૅୖ᰾̘ɿәቆવɿɖᖅໞֳଉ ɿᆎᨀ౯Ԅଉ ଉ ɿଏԆֳଉ ɿ୮ᚊ Iଉ ఎগકগકрἕ۰ᥴకકಊᢼᥴకકଗფࢫ816-8580 ᱨ᭔ᆎᅠలᆎᅠӸ 6-1 ଉఎগકগકрἕ۰ᥴకકᮾ᳣рᢼᲇકȤϘࢫ816-8580 ᱨ᭔ᆎᅠలᆎᅠӸ 6-1 ଉ ଉ ሱBAHAM ཪᮾࢫ150-6019 ኇ̸ȩগᨀٚኇ‫ؤ‬ŋ 2-3-6-201A ceramic coating slurry was designed, which suspended or dissolved ceramic components silica, titania, alumina and kaolinite and glass-forming components alkali silicates and soda ash in water. SiO 2 -Al 2 O 3 -TiO 2 based composite films about 100 mm thick were deposited on a steel plate by coating the slurry with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Previously we reported that the ceramic grains coagulated together more heavily to give smooth and less porous surface morphology, when the addition of glass-forming-components to the non-milled coating increaced. 15,16 Composition ratio for H-1 coating nonmilled was decided finally under such deep investigations. However it is turned out that the milled case gives smoother surface effectively.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Previously we reported that the ceramic grains coagulated together more heavily to give smooth and less porous surface morphology, when the addition of glass-forming-components to the non-milled coating increaced. 15,16 Composition ratio for H-1 coating nonmilled was decided finally under such deep investigations. However it is turned out that the milled case gives smoother surface effectively.…”
Section: Methodsmentioning
confidence: 99%
“…The porous nature of the coating pre-calcined at 420c C or calcined at 800c C was obvious from the SEM images, but it was almost impossible to identify the through-holes of the coatings from such observations. Although we previously tried to visualize the through-holes by Cu electrochemical deposition method, 16 the method, when such pores were very small, seemed to be very difficult. In fact, no Cu-deposition was observed in the H-4b, H-5b and H-6b coatings.…”
Section: Evaluation Of Though-holementioning
confidence: 99%
See 2 more Smart Citations